PKM Utilization of Podcasts as Communication Media for Da'wah Broadcasting during the Covid Outbreak - Mohammad Bahrul Ulum; Nanang Qosim; Abdur Rahmad; Abdul Qohhar; Mohammad Badrus Soleh; M. Saifillah; Muhammad Effendi (Universitas Nurul Jadid, 2021)
The COVID-19 pandemic requires people to adapt to current conditions that prohibit activities involving large numbers of people or create a crowd of people. Society is faced with virtual conditions in every situation activity, especially in religious activities. The places of worship are commonly closed. Today the implementation of prayer in the congregation is used to avoid the spread of covid 19. This article aims to report the results of community service related to the use of podcasts as a medium of communication broadcasting da'wah in mosques. This service activity also provides convenience for mosque administrators in the East Probolinggo area to deliver propaganda. This service is expected to help mosque administrators understand and use podcasts to communicate religious activities. And able to use social media and communication media to deliver spiritual information and da'wah.